Effect of the composition on the morphology and mechanical properties of nanoporous carbon monoliths derived from phenol–formaldehyde/poly(methyl methacrylate) blends. Issue 22 (10th November 2015) - Wang, Xiaopeng; Luo, Zhenhua; Chen, Fenghua; Ye, Li; Li, Hao; Zhao, Tong
Abstract: Abstract : Nanoporous carbon monoliths with different pore structures were obtained by carbonizing cured phenol–formaldehyde (PF) resin/poly(methyl methacrylate) (PMMA) blends. The effect of the molecular weight of PMMA, reaction activity of PF, and content ratio of compositions on the pore structure of carbon monoliths was systematically investigated, with emphasis on controlling the morphology of the nanostructure and pore size distribution. Nanostructures were an important factor in determining the compressive strength of porous carbon monoliths. The relationship between the nanoporous structure of carbon monoliths and compressive strength was revealed. Co-continuous pores provided escape channels for those volatile gases produced in the carbonization process to escape, reducing inner stress of the carbon materials. During compressive loading, co-continuous pores could also help to scatter and absorb the stress and energy. Porous carbon monoliths with a compressive strength of 34 MPa were obtained, and the compressive strength increased by 580% compared with that of carbon monoliths obtained from pure PF.